Trade beyond the margins : cross-border traders between Zambia and South Africa - Clarke, Jumani (Department of Sociology, 2023)
In the week leading up to Christmas day, the border between South Africa and Zimbabwe is a very busy place. The road up to the border post, at the Beitbridge bridge over the Limpopo River, is a kilometres long snaking queue of cars, buses and trucks, waiting for hours before they go through the routine customs checks and stamps. Most passengers, who are quite naturally eager to stretch their limbs and escape the heat, abandon their vehicle and driver and walk ahead for the remaining distance to the front of the queue for shade and refreshments. But strangely, this is not a flood of Africans coming into South Africa in search of work or mischief over South Africa's holiday season. Instead, it is the exodus of people heavy with groceries, fashionable accessories and various hardware going in the direction of their home countries. In the queue are mostly Zimbabweans, Zambians, Malawians and some nationals from the Democratic Republic of Congo, on the return leg of a brief shopping trip to South Africa, the land of shops and malls.